Deviant bodies : critical perspectives on difference in science and popular culture - Terry, Jennifer (1995)
Introduction: Mapping embodied deviance / Jacqueline Urla and Jennifer Terry. - Gender, race, and nation: the comparative anatomy of "Hottentot" women in Europe, 1815-1817 / Anne Fausto-Sterling. - Framed: the deaf in the Harem / Nicholas Mirzoeff. - Colonizing and transforming the criminal tribesman: the Salvation Army in British India / Rachel J. Tolen. - This norm which is not one: reading the female body in Lombroso's anthropology / David G. Horn. - Anxious slippages between "us" and "them": a brief history of the scientific search for homosexual bodies / Jennifer Terry. - The Destruction of "Lives not worth living" / Robert N. Proctor. - Domesticity in the Federal Indian schools: the power of authority over mind and body / K. Tsianina Lomawaima. - Nymphomania: the historical construction of female sexuality / Carol Groneman. - Theatres of madness / Susan Jahoda. - The Anthropometry of Barbie: unsettling ideals of the feminine body in popular culture / Jacqueline Urla and Alan C. Swedlund. - Regulated passions: the invention of inhibited sexual desire and sexual addiction / Janice M. Irvine. - Between innocence and safety: epidemiologic and popular constructions of young people's need for safe sex / Cindy Patton. - The Hen that can't lay an egg (Bu xia dan de mu ji): conceptions of female infertility in modern China / Lisa Handwerker. - The Media-ted gene: sotries of gender and race / Dorothy Nelking and M. Susan Lindee